Prinsip-Prinsip Penyampaian Pesan Dalam Al Qur’an Perspektif Tafsir Al-Azhar - Sopiyan, Wawan; Berlian, Zainal; Mislawaty, Sri Eva (El-Ghiroh : Jurnal Studi Keislaman, 2023)
The Quran contains teachings that regulate human life in all aspects and its teachings apply at all times. The teachings in the Koran are universal, which means that the teachings of the Quran can be practiced by all mankind. This is no exception regarding communication as a human activity in everyday life. This research attempts to find the principles of conveying messages in the Al-Qur'an from the perspective of Tafsir Al-Azhar by Buya Hamka. The research was conducted using a literature review method (library research). Researchers explore data and information from the Quran, the Book of Hadith, the Book of Tafsir, journals, books, documents, records of historical stories or pure literature research related to the research object. The research results found that the principles of conveying messages in the Al-Quran include: Qoulan Sadida, Qoulan Ma'rufa, Qoulan Baligha, Qoulan Maiysura, Qoulan Layyina, Qoulan Karima. The values ​​taught in these principles are honesty, justice, kindness, straight, smooth, polite, appropriate, respectful, solemn, optimistic, beautiful, pleasant, logical, eloquent, clear, precise, touching, harmonious, impressive, calm, effective, gentle, generous, gentle, and humble.